Pengaruh kompetensi aparatur desa dan pengawasan terhadap pengelolaan dana desa pada desa di kecamatan menganti kabupaten gresik - Julistioningsih, Azizah; Tituk Diah Widajantie (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to test and prove the effect of the competency variable of the village apparatus on the variable of village fund management in villages in Menganti District. This study uses a quantitative method. The location of the research was carried out in villages located in Menganti District, Gresik Regency. The sampling technique used is purposive sampling and the type of data in this study is primary data. The data collection technique used in this study was through the distribution of questionnaires or questionnaires to respondents. The technical analysis used in this study uses the SmartPLS 3.0 application. The results of this study indicate that the competence of the village apparatus has an effect on the management of village funds, while supervision has no effect on the management of village funds.